Abundance and Distribution of Zooplankton along Phang Rad River, Klaeng District, Rayong Province - Phudhom, Alongkorn; Tangkrock-olan, Nongnud (Burapha Science Journal, 2026)
Abundance and distribution of zooplankton and environmental factors along Phang Rad River were studied on five different stations, i.e., Pang Rad estuary (ST1), Urban areas (ST2), Oyster farming areas (ST3), Shrimp farming areas (ST4), and Tha Kong River branch (ST5), during May 2018 to April 2019. Zooplankton samples were collected using a plankton net with a mesh size of 150 micrometers. A total of 53 taxa from 14 zooplankton phyla were found. From that, 29 taxa were holoplankton while 24 taxa were meroplankton. The most abundance was the Phylum Arthropoda (83.88%), following by Mollusca and Annelida. Calanoid copepods were the dominant group found in this study. For all year round, the highest abundance of zooplankton was found in May (63.42±22.05 x102 ind./m2) following by June (62.19±5.47 x102 ind./m2), December (57.46±10.53 x102 ind./m2), and November (52.91±12.08 x102 ind./m2), respectively. Comparing with the study areas, ST1 had the highest abundance (50.46±27.64 x102 ind./m2) following by ST2 (46.07±17.16 x102 ind./m2), ST3 (40.82±14.07 x102 ind./m2) and ST5 (33.46±15.78 x102 ind./m2), respectively. The lowest abundance was found in the ST4 (32.17±15.04 x102 ind./m2). The results from this study can help understand the abundance and distribution of zooplankton throughout the year, and the results can be used as a guideline for setting a standard measurement for the conservation of zooplankton resources in the Pang-Rad river in the future.